2023
DOI: 10.1111/nph.19072
|View full text |Cite|
|
Sign up to set email alerts
|

SlMPK1‐ and SlMPK2‐mediated SlBBX17 phosphorylation positively regulates CBF‐dependent cold tolerance in tomato

Abstract: Summary B‐box (BBX) proteins are an important class of zinc finger transcription factors that play a critical role in plant growth and stress response. However, the mechanisms of how BBX proteins participate in the cold response in tomato remain unclear. Here, using approaches of reverse genetics, biochemical and molecular biology we characterized a BBX transcription factor, SlBBX17, which positively regulates cold tolerance in tomato (Solanum lycopersicum). Overexpressing SlBBX17 enhanced C‐repeat binding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Due to the large number of members of its large family, they will inevitably be positively or negatively regulated by TFs. Some key ion channel proteins are required to remain silent under normal conditions and are activated when stress is generated, such as the above-mentioned that OsWRKY53 acts directly on OsHKT1;5 and deregulates transcriptional repression of OsHKT1;5 under salt stress (Yu et al, 2023). Here, we clearly showed that the Cluster IIA HAK transporters OsHAK2 and OsHAK7 were directly transcriptionally regulated by OsBBX17 (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Due to the large number of members of its large family, they will inevitably be positively or negatively regulated by TFs. Some key ion channel proteins are required to remain silent under normal conditions and are activated when stress is generated, such as the above-mentioned that OsWRKY53 acts directly on OsHKT1;5 and deregulates transcriptional repression of OsHKT1;5 under salt stress (Yu et al, 2023). Here, we clearly showed that the Cluster IIA HAK transporters OsHAK2 and OsHAK7 were directly transcriptionally regulated by OsBBX17 (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, our study followed a very similar pattern to a recent study on OsWRKY53, which trans-repressed OsHKT1;5 to negatively regulate rice salt tolerance. Meanwhile, OsMKK10.2 and OsMPK6 are positive regulators of salt tolerance (Yu et al, 2023). Differently, OsMPK6 activates OsWRKY53 to weaken OsMKK10.2-OsMPK6 signaling and protect plants from overreacting to salinity (Yu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations